Pelimpahan Kewenangan Bupati Kepada Camat Dalam Mewujudkan Efektifitas Penyelenggaraan Kecamatan Pada Pemerintah Kabupaten Pandeglang, Provinsi Banten - Miftah Faiz Ali Ramdhani; Nopi Andayani (Universitas Serang Raya, 2023)
This article examines the sub-district institution in Pandeglang Regency's ability to implement its capacity as an autonomous region feature as well as the administrative region feature of universal government administration, as well as the fulfillment of the necessary condition element. It also offers a recommendation model for the delegation of Regent authority to the sub-district head based on the empirical situation. Attempts at the research were made utilizing a qualitative methodology. The study's findings demonstrate that in the Pandeglang Regency, the legal authority granted by the Regent is still not directly correlated with the fulfillment of necessary condition elements of sub-district institutions like human resources and budget. Then, in terms of the camat's or district's legal authority, some aspects—such as the alteration of laws and regulations, regional characteristics, the spirit of institutional strengthening in public services, and the requirements of coordinating national development programs—remain to require some adjusting. In order to achieve the efficacy of the sub-district institution in the administration of regional government, the Pandeglang district government is expected to implement a number of arrangements and restructuring of the sub-district institution under the suggested model. Keywords: Delegation of authority, effectiveness of administration, sub-district institution